Trends of multidrug resistance phenotypes in vibrio cholerae causing cholera in Bangladesh - Afzal, Ahmed Rafi (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.